(untitled) (Sound Stage Screen, 2025)
Review of Megan Steigerwald Ille, Opera for Everyone: The Industry’s Experiments with American Opera in the Digital Age, University of Michigan Press, 2024. 308 pp. ISBN 9780472904303.